The Effect of Profit Sharing Ratio on Customer Interest in Savings in Time Deposit Products at Bank Mega Syariah KC Medan - Yumna Syifa; Mustopa Khamal Rokan (Penerbit Jurnal Indonesia, 2022)
Banking is a financial institution that provides services and conveniences to its customers who wish to conduct financial transactions. Bank Mega Syariah KC Medan is one of the Islamic financial institutions that offers mudharabah time deposits (deposits) with profit sharing contracts. The target of this bank product is some people who can afford and have excess funds. This study aims to determine the effect of the profit-sharing ratio on customer interest in saving on deposit products against Mega Syariah Bank KC Medan. The advantage of this profit-sharing ratio system for banks is that it can increase investment in third-party funds, as well as facilitate the circulation of money within the bank.